A Study of Collaborative Skills: Comparing the Effectiveness of ARIAS Interest and TS-TS Models in Elementary Education - Hanifah, Anis; Handayani, Sri Lestari (FKIP - Universitas Riau, 2025)
The development of 21st-century skills, particularly student collaboration, has become increasingly important in elementary education. This study aims to compare the effectiveness of the ARIAS learning model (Interest type) and the Two Stay Two Stray (TS-TS) model in enhancing student collaboration during Integrated Science and Social Studies (IPAS) learning among fifth-grade students. The research employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. Two classes from SDN Cengkareng Barat 16 Pagi were selected as samples, with each class implementing one of the two learning models. Data were collected through validated observation sheets designed to measure student collaboration levels. The results revealed a significant difference in collaboration levels between the two experimental groups, with the TS-TS model demonstrating a greater positive impact on students' collaborative abilities compared to the ARIAS (Interest type) model. Statistical analysis confirmed that the TS-TS approach was more effective in fostering teamwork, communication, and peer interaction skills. These findings suggest that the TS-TS model is a more suitable learning strategy for enhancing student collaboration in IPAS subjects, providing valuable insights for educators seeking to implement collaborative learning approaches in elementary integrated curriculum settings.